2019
DOI: 10.1016/j.rser.2019.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria evaluation of renewable energy alternatives for electricity generation in a residential building

Abstract: The residential sector is well known to be one of the main energy consumers worldwide. The purpose of this study is to select the best renewable energy alternatives for electricity generation in a residential building by using a new integrated fuzzy multi-criteria group decision-making method. In renewable energy decision-making problems, the preferences of experts and decision-makers are generally uncertain. Furthermore, it is challenging to quantify the reel performance of renewable energy alternatives using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 84 publications
(169 reference statements)
0
25
0
1
Order By: Relevance
“…Li et al [9] developed a fuzzy AHP based tool to evaluate the carbon performance of public projects by ranking different carbon emission criteria related to the design, construction, and operation phases of these projects. Other examples of using FAHP to rank the different economic, social, and environmental impacts of sustainable technologies also exist [18,19]. Malik et al [20] provide a ranking for the following five sustainable project characteristics: technology, economic impact, environmental impact, planning time, and policy to aid in the selection between alternative sustainable projects in Oman.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [9] developed a fuzzy AHP based tool to evaluate the carbon performance of public projects by ranking different carbon emission criteria related to the design, construction, and operation phases of these projects. Other examples of using FAHP to rank the different economic, social, and environmental impacts of sustainable technologies also exist [18,19]. Malik et al [20] provide a ranking for the following five sustainable project characteristics: technology, economic impact, environmental impact, planning time, and policy to aid in the selection between alternative sustainable projects in Oman.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To this aim, several solutions have been proposed that include photovoltaic (PV) systems, thermophotovoltaic (PV-T) for electricity and thermal generation and co-generation and tri-generation using gas, solar or biomass as the main driver, fuel cells and Stirling engines, investigated for instance by Calise et al and Seddiki and Bennadji [7,8]. However, the implementation and optimization of systems that include two or more energy sources to provide heating, cooling, domestic hot water (DHW) and electricity at the same time are still in their early stages and require further efforts in the definition of the best strategies and solutions for each type of building [9,10]. The vast majority of works in the literature relate to residential buildings for which extensive reviews on different existing alternatives can be found [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…This is because linguistic information is transformed into real numbers, and uncertain decisions are transformed into precise categories. To some extent, this violates the original intention of using fuzzy methods [33,34]. When a single term cannot accurately express the evaluation information of an object, researchers propose uncertain linguistic variables, but a rough description of the uncertainty of qualitative information is inevitable, which will also lead to information distortion [35,36].…”
Section: Introductionmentioning
confidence: 99%